Review of marketing research. Vol. 3 - Malhotra, Naresh K. (Review of marketing research,, 2007)
"The Review of Marketing Research annual series provides current, state-of-the-art articles by the marketing field's leading researchers and academicians. In contrast to other research publications in the field that impose rigid limitations on the length of articles, 'RMR' publishes longer chapters that are not only theoretically rigorous, but also offer richer detail, including literature reviews, cutting-edge methodologies, empirical studies, emerging trends, international developments, guidelines for implementation, and suggestions for future theory development and testing.Edited by Naresh K. Malhotra along with a distinguished editorial review board drawn from the leading figures in marketing research and theory, the annual 'RMR' volumes include approximately 7-8 chapters. Each contribution undergoes a double-blind review process, and each volume represents an across-the-board view of the full range of current marketing research methodologies. No marketing bookshelf or library will be complete without this annual series."